Clinical and laboratory presentations of Janus Kinase II-positive patients in Saudi population - H Malhan; H Alzahrani; Ghada M Elgohary; T Owaidah; M Aslam; Said Yousuf Mohamed (Journal of Applied Hematology, 2014)
Introduction: Janus Kinase II (JAK-II) mutation has a pivotal role in the pathogenesis of the myeloproliferative neoplasms (MPN) and has been shown to be involved in thrombotic complications of these diseases. However, there are limited data regarding clinic-biological features and cytogenetic abnormalities in the Saudi population. Aim: The main aim of this study was to examine clinical presentations, laboratory findings and prognosis of JAK-II-positive Saudi population referred to KFSHRC for testing for variable indications. Methods: A total of 200 patients was referred to our institute for JAK-II mutation testing by polymerase chain reaction based on clinical/laboratory suspicion; about 102 (51%) proved positive. Of the positive cohort, only 62 patients had completed evaluable medical records. Results: Their mean age was 48.2 (range: 16-81) years and 51.6% were males. About 75% had symptoms such as headache 13 [21%]; pruritus 9 [14.5%], visual 7 [11.3%], erythromelalgia 2 [3.2%], and none specific symptoms like fatigue/weakness abdominal discomfort in 30 (48.2%) while the remaining 25% were diagnosed incidentally from abnormal complete blood cells. Clinic-radiological features included: Splenomegaly (53.6%), hepatomegaly (24%), and skin lesions (8%). Thrombosis of portal, hepatic, splenic and mesenteric veins was seen in 24%, stroke and transient ischemic attack in 14%, deep vein thrombosis and pulmonary embolism in 11.2%, ischemic heart disease in 9.6% and 3.2% had arterial thrombosis. The mean peripheral blood count showed white blood cell 13.3 × 109/l, hemoglobin 147.3 g/l and platelets 714 × 109/l. Of the 35 patients evaluated by bone marrow biopsy, the majority (80%) had hyperculluarity. Cytogenetic abnormalities were found in 7 (20%) of the 35 patients and one patient had both JAK-II and BCR/ABL mutations. All the positive patients except 3 (4.8%) were diagnosed as MPNs, 29 (46.7%) polycythemia vera, 24 (38.7%) essential thrombocythemia, 2 (3.2%) primary myelofibrosis and MPN-not otherwise specified in 1 (1.6%). Treatment modalities including hydroxyurea, anagrelide, and thalidomide were used in 75%, antiplatelets were used in nearly 2/3 (61.3%) and 29% of patients required anticoagulants. Three-year actuarial survival was 87% with death related mainly to progressive fibrosis and cytopenia, thrombotic complications necessitating major surgeries, pneumonia or sepsis.